The potential impact of COVID-19 vaccination on patients with immune thrombocytopenic purpura: A protocol for systematic review and meta-analysis. - Yangyang Li; Demin Kong; Yicheng Ding; Jinhuan Wang (PLoS ONE)
Background Immune thrombocytopenic purpura (ITP) is a disease characterized by a decrease in platelet count, which can be triggered by various factors, including viral infections and vaccination. With the widespread vaccination against COVID-19, concerns have arisen regarding a possible link between the vaccine and the exacerbation of ITP. This study aims to comprehensively evaluate the impact of COVID-19 vaccination on ITP patients, including associated risks and outcomes. Methods A comprehensive search will be conducted in multiple electronic databases (including PubMed, Web of Science, EMBASE, Cochrane Library, CNKI, Wan Fang, VIP, and CBM) to identify relevant studies. This study will include randomized controlled trials, cohort studies, case-control studies, and case series evaluating the impact of COVID-19 vaccination on ITP patients. The primary outcome measure is the change in platelet count, while secondary outcome measures include the occurrence of thromboembolic events, bleeding complications, ITP recurrence rate, impact of ITP exacerbation, and adverse events. Data will be summarized and analyzed using Review Manager Software (RevMan) V.5.4. In addition, subgroup analyses will be performed to explore potential sources of heterogeneity. Results It is anticipated that different types of COVID-19 vaccines may have varying impacts on ITP patients, leading to potential differences in outcomes. This study aims to comprehensively evaluate the potential impact of COVID-19 vaccination on ITP patients and provide reference for clinical decision-making. Conclusions The results of this systematic review and meta-analysis will provide crucial information on COVID-19 vaccination for ITP patients and clinicians, contributing to guiding vaccination decisions and monitoring potential impacts after vaccination.